2014
DOI: 10.3109/21678421.2014.990036
|View full text |Cite
|
Sign up to set email alerts
|

Factors affecting longitudinal functional decline and survival in amyotrophic lateral sclerosis patients

Abstract: Background

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

14
54
6
1

Year Published

2015
2015
2023
2023

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 80 publications
(75 citation statements)
references
References 32 publications
14
54
6
1
Order By: Relevance
“…Notably, only some of these factors resulted also independent prognostic factors for ALS survival (age, site of onset and DFS), suggesting that survival and ALSFRS-R can be influenced by different factors. These findings, are in accordance with a recent Japanese study [16], and could be explained by the : a progressive decline in the ALSFRS-R total score may represent loss of one or more functions affecting in different ways ALS survival as patients with the same score may have very different progression and clinical presentation. For example, score 0 or 1 at item 12 (respiratory insufficiency) of the ALSFRS-R has a different meaning in terms of survival than a score 0 or 1 at item 9 (climbing stairs).…”
Section: Discussionsupporting
confidence: 91%
See 1 more Smart Citation
“…Notably, only some of these factors resulted also independent prognostic factors for ALS survival (age, site of onset and DFS), suggesting that survival and ALSFRS-R can be influenced by different factors. These findings, are in accordance with a recent Japanese study [16], and could be explained by the : a progressive decline in the ALSFRS-R total score may represent loss of one or more functions affecting in different ways ALS survival as patients with the same score may have very different progression and clinical presentation. For example, score 0 or 1 at item 12 (respiratory insufficiency) of the ALSFRS-R has a different meaning in terms of survival than a score 0 or 1 at item 9 (climbing stairs).…”
Section: Discussionsupporting
confidence: 91%
“…Since now ALSFRS-R has been studied in patients included in clinical trials or in patients attending a tertiary ALS Centre [16], with a limited generalizability of the studies' findings to the entire ALS population, due to exclusion of the elderly and more advanced patients [21], and to exclusion of the patients who do not meet El Escorial Criteria for probable or definite ALS.…”
Section: Discussionmentioning
confidence: 99%
“…Previous epidemiological studies have shown several factors related to shorter survival in ALS: older age (6,15,16), bulbar onset (15,16,17), a reduction in forced vital capacity (16), a rapid reduction in body mass index (18,19), a rapid decrease in the revised ALS Functional Rating Scale (ALSFRS-R) score (16,20), and psychosocial factors (21). A high ALSFRS-R score at TIV initiation also predicts a long-term survival after TIV (22).…”
Section: Discussionmentioning
confidence: 99%
“…In Japan and South Korea, the mean age of disease onset is 61 and 58 years, respectively,11 12 but other Asian cohorts have suggested a younger age of disease onset compared with Caucasians. In China, the mean age is approximately 52 years,13–15 whereas in a single study from India, the age of onset was 46 years 16.…”
Section: Epidemiologymentioning
confidence: 99%